PENGARUH KEMUDAHAN DAN KEAMANAN TERHADAP LOYALITAS PELANGGAN E-WALLET APLIKASI DANA - Desi Wahyuningsih; Lia Nirawati (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
Technology is experiencing very rapid development, especially internet-based technology. The purpose of this study was to determine the effect of convenience and security on customer loyalty of the E-wallet Dana in Surabaya. This type of research used is quantitative research. This study uses primary data, namely data directly through questionnaires which are filled in directly by the respondents. The population taken is E-wallet Dana users who have used E-wallet Dana at least 3 times. The sampling technique used non-probability sampling with the sampling method using purposive sampling. With a total of 100 respondents who have made transactions on the application of Dana at least 3x. By using data analysis techniques, namely multiple linear regression analysis. Based on the results of the study, it can be concluded that the convenience and security variables simultaneously have a positive effect on customer loyalty for the E-wallet Dana; The convenience variable partially has a positive and significant effect on E-wallet Dana Customer Loyalty; The Security Variable partially has a positive and significant effect on E-wallet Dana Customer Loyalty